2012
DOI: 10.1002/lapl.201110118
|View full text |Cite
|
Sign up to set email alerts
|

Efficient diode-end-pumped Yb:CaNb2O6 thin-disk laser at 1003 nm and second-harmonic generation for an emission at 501.5 nm

Abstract: Thanks to its high emission cross section around 1 µm, Yb:CaNb2O6 is a good candidate for laser operation near 1 µm as shown in our figure of merit. We demonstrated, for the first time to our knowledge, laser operation of Yb:CaNb2O6 at 1003 nm. More than 2.23 W at 1003 nm and 577 mW at 501.5 nm were produced simultaneously. This visible wave length corresponds to an iodine transition previously studied with argon ionized lasers for metrological applications. (© 2012 by Astro Ltd., Published exclusively by WILE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Niobates have attracted a great deal of attention in several devices due to their commendable electro-optical, photoelastic, piezo-electric, and nonlinear properties together with good mechanical and chemical stability and a wide transparency range. , The luminescence properties of rare earth ions-doped phosphors such as YNbO 4 :Eu 3+ , GdNbO 4 :Tm 3+ , Dy 3+ , and La 3 NbO 7 :Eu 3+ have been investigated in detail, ,, which are related to the host sensitization via energy transfer from host to activators based on energy matching of host photoluminescence (PL) emission and activators excitation spectra. CaNb 2 O 6 , a subcomponent of the complex perovskite family A­(B′ 1/3 B″ 2/3 )­O 3 , crystallizing with orthorhombic columbite structure in the space group of Pbcn (60), has been investigated as a blue luminescence material, a good dielectric material for microwave dielectric applications, a catalyst for photocatalytic splitting of water, a strong source of coherent light which can be useful in applications of holography, as well as laser host material. In 2007, Boutinaud et al have investigated the dependence of PL properties of Tb 3+ -doped CaNb 2 O 6 on temperature . In 2011, Huang et al have shown the PL of CaNb 2 O 6 :Eu 3+ under 393 nm excitation .…”
Section: Introductionmentioning
confidence: 99%
“…Niobates have attracted a great deal of attention in several devices due to their commendable electro-optical, photoelastic, piezo-electric, and nonlinear properties together with good mechanical and chemical stability and a wide transparency range. , The luminescence properties of rare earth ions-doped phosphors such as YNbO 4 :Eu 3+ , GdNbO 4 :Tm 3+ , Dy 3+ , and La 3 NbO 7 :Eu 3+ have been investigated in detail, ,, which are related to the host sensitization via energy transfer from host to activators based on energy matching of host photoluminescence (PL) emission and activators excitation spectra. CaNb 2 O 6 , a subcomponent of the complex perovskite family A­(B′ 1/3 B″ 2/3 )­O 3 , crystallizing with orthorhombic columbite structure in the space group of Pbcn (60), has been investigated as a blue luminescence material, a good dielectric material for microwave dielectric applications, a catalyst for photocatalytic splitting of water, a strong source of coherent light which can be useful in applications of holography, as well as laser host material. In 2007, Boutinaud et al have investigated the dependence of PL properties of Tb 3+ -doped CaNb 2 O 6 on temperature . In 2011, Huang et al have shown the PL of CaNb 2 O 6 :Eu 3+ under 393 nm excitation .…”
Section: Introductionmentioning
confidence: 99%
“…In 1969, Kaminskii et al reported the absorption and luminescence spectra of Nd:CaNb 2 O 6 [17]. As the rare earth ion-doped CaNb 2 O 6 crystal can be used as a laser crystal, many research studies on its fundamental laser have been reported [18][19][20][21][22]. In 1977, Husson et al found that the CaNb 2 O 6 crystal was also an excellent Raman crystal with a primary Raman shift of 904 cm −1 , and the polarized Raman spectra in different directions were measured [23] [25].…”
Section: Introductionmentioning
confidence: 99%